After the Berger Blanc: A Comparative Approach to the Utilitarian Regulation of Municipal Animal Control - Lazare, Jodi (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2013)
In April 2011, Radio-Canada aired an investigative report exposing the cruel treatment of domestic animals by workers at one of Montreal’s largest animal shelters. A private business, the Berger Blanc held the majority of municipal contracts for animal control services throughout Montreal. Following the widely-watched exposé, the regulation of domestic animal welfare rose to the top of the agenda both at Montreal’s City Hall and Quebec’s National Assembly, as citizens demanded a response to the jarring images of cruelty and neglect. The province responded, adopting a regulation to strengthen the legal protection of dogs and cats under Quebec’s Animal Health Protection Act— a regulation which has been criticized as ineffective and inadequate by animal welfare groups throughout the province. Similarly, Montreal’s City Hall announced steps to launch a municipal animal control service. And yet, progress is slow and many Montreal boroughs continue to renew their contracts with the Berger Blanc. This paper will review the theoretical, political and legal context surrounding the issue of domestic animals, and employ an animal welfarist (utilitarian) approach to examine the three traditional municipal animal control service models, namely the private for-profit model, the private non-profit model and the public model. In doing so, the paper will suggest that despite the municipal government’s stated financial priorities, the only solution to Montreal’s domestic animal situation—one which properly takes the equal interests of domestic animals into account—lies in a publicly-funded, municipally-run animal services department, similar to the model currently employed by the City of Calgary.